1996
DOI: 10.1046/j.1365-2141.1996.d01-1743.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel delivery system for continuous desferrioxamine infusion in transfusional iron overload

Abstract: Fifteen iron-overloaded thalassaemia major (TM) patients and two homozygous sickle cell patients (SCD) were treated continuously for 7d each week with the novel 48 h continuous subcutaneous (s.c.) desferrioxamine (DFX) delivery device (code C1083, Baxter) and 10 TM patients received the 24 h continuous intravenous (i.v.) DFX delivery device (code C1071). The 27 patients had previously received conventional s.c. DFX for 8-10h on 5 or more days each week. The serum non-transferrin bound iron (NTBI) levels fell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…Our data show that continuous low-dose s.c. DFO infusion using the C 1083 infusor has been effective in reducing iron overload, as already shown by others [16], and in preventing allergic reactions. With this device we have transformed three noncompliant into highly compliant s.c. DFO patients.…”
Section: Discussionmentioning
confidence: 75%
“…Our data show that continuous low-dose s.c. DFO infusion using the C 1083 infusor has been effective in reducing iron overload, as already shown by others [16], and in preventing allergic reactions. With this device we have transformed three noncompliant into highly compliant s.c. DFO patients.…”
Section: Discussionmentioning
confidence: 75%
“…In conditions of non-iron overload, however, this toxicity is prevented by the presence of transferrin that sequesters the iron. It has also been shown that release of iron from Hb when these systems are exposed to H 2 O 2 is limited [59], leading to the complications arising from the excess iron [66][67][68]. α-Hydroxypyridinones are an orally active alternative to desferrioxamine in treatment of iron overload [69][70][71][72].…”
Section: Iron Chelators and Oxidative Stressmentioning
confidence: 99%
“…In the early years of the study, maximal 12-hour infusions were possible through mechanical pumps (up to 60 mg/kg per day). After 1994, subcutaneous DFO was given through 24-hour disposable balloon infusers 22 at doses of 40 to 60 mg/kg per day up to 7 days a week. The third modality was continuous 24-hour intravenous infusion of DFO (100 mg/kg) diluted in 500 to 1000 mL normal saline and delivered though a peripheral vein on an inpatient basis for up to 1 week at a time to supplement ongoing subcutaneous treatment.…”
Section: Methodsmentioning
confidence: 99%